Outcomes of transcatheter vs surgical aortic valve replacement in pre-existing chronic liver disease patients: A meta-analysis of observational studies - Aizaz Ali; Muhammad Abdullah Ali; Asad Iqbal Khattak; Fazia Khattak; Abdullah Afridi; Touba Azeem; Umme Salma Shabbar Banatwala; Umama Alam; Ayesha Khan; Urba Jalal; Abdul Moeez; Malik W.Z. Khan; et al. (International Journal of Cardiology: Heart & Vasculature)
Aortic valve stenosis in patients with chronic liver diseases, particularly liver cirrhosis and End-Stage Liver Disease, poses significant management challenges due to the interplay between cardiovascular and hepatic dysfunction. This systematic review and meta-analysis compared the safety and efficacy of Transcatheter Aortic Valve Replacement (TAVR) and Surgical Aortic Valve Replacement in this high-risk population. An extensive search of PubMed, Embase, and Web of Science (inception to January 5, 2025) identified 11 retrospective studies comprising 19,097 patients. Risk ratios for dichotomous outcomes and mean differences (MD) for continuous outcomes, each with 95% confidence intervals, were calculated using random-effects models.The analysis revealed that TAVR significantly reduced hospital mortality (RR 0.36, 95 % CI: 0.30–0.42; I2 = 7.6 %), acute kidney injury (RR 0.51, 95 % CI: 0.33–0.78; I2 = 57.2 %), bleeding (RR 0.33, 95 % CI: 0.28–0.39; I2 = 0.0 %), stroke (RR 0.35, 95 % CI: 0.23–0.51; I2 = 6.1 %), and blood transfusion (RR 0.48, 95 % CI: 0.40–0.57; I2 = 7.6 %). TAVR was also associated with shorter hospital stays (MD −6.77 days, 95 % CI: −9.17 to −4.38; I2 = 97.5 %). No significant differences were observed in vascular complications requiring surgery or hospital charges and post-operative infections.These findings suggest TAVR offers significant advantages over SAVR in reducing complications such as mortality, acute kidney injury, and bleeding in patients with liver disease. However, further randomized trials are necessary to confirm long-term outcomes and establish optimal treatment strategies for this high-risk population.